2023
DOI: 10.1186/s13046-023-02675-4
|View full text |Cite
|
Sign up to set email alerts
|

Disulfidptosis: a new target for metabolic cancer therapy

Abstract: Altered metabolism is a hallmark of cancer and presents a vulnerability that can be exploited in cancer treatment. Regulated cell death (RCD) plays a crucial role in cancer metabolic therapy. A recent study has identified a new metabolic-related RCD known as disulfidptosis. Preclinical findings suggest that metabolic therapy using glucose transporter (GLUT) inhibitors can trigger disulfidptosis and inhibit cancer growth. In this review, we summarize the specific mechanisms underlying disulfidptosis and outline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
61
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(107 citation statements)
references
References 5 publications
0
61
0
Order By: Relevance
“…Actin networks can collapse if the disulfide bonds among proteins are not repaired, leading to cell death. Disulfidptosis, a novel type of cell death, has been excavated recently, and disulfidptosis regulators are screened, which will ultimately contribute to the advancement of therapeutic approaches targeting cancer 41 . It is crucial to recognize the underlying mechanisms of disulfidptosis, as they have significant impacts on understanding the fundamentals of cellular homeostasis, as well as providing insight into treatment of diverse diseases such as cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Actin networks can collapse if the disulfide bonds among proteins are not repaired, leading to cell death. Disulfidptosis, a novel type of cell death, has been excavated recently, and disulfidptosis regulators are screened, which will ultimately contribute to the advancement of therapeutic approaches targeting cancer 41 . It is crucial to recognize the underlying mechanisms of disulfidptosis, as they have significant impacts on understanding the fundamentals of cellular homeostasis, as well as providing insight into treatment of diverse diseases such as cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is urgent to identify reliable prognostic signatures for early prognosis to facilitate the diagnosis and treatment of ovarian cancer. Recently, emerging research reported that, disul dptosis, a newly discovered type of non-programmed cell death characterized by iron accumulation and lipid peroxidation, was closely associated with various physiological and pathological processes in cancer development 14 . However, the landscape of disul dptosis in ovarian cancer remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, as the underlying mechanism of disulfidptosis has been discovered, the potential link between disulfidptosis‐related genes (DRGs) and AD remains unclear. Currently, studies on disulfidptosis have mainly focused on cancers 18–20 . A recent study has reported that the dysregulation of actin cytoskeletal dynamics is associated with the pathology of AD 21 .…”
Section: Introductionmentioning
confidence: 99%